2020
DOI: 10.1101/2020.09.24.20191411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 within the healthcare environment: a multicentre study conducted during the first wave of the COVID-19 outbreak in England

Abstract: Understanding how Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is spread within the hospital setting is essential if staff are to be adequately protected, effective infection control measures are to be implemented and nosocomial transmission is to be prevented. The presence of SARS-CoV-2 in the air and on environmental surfaces around hospitalised patients, with and without respiratory symptoms, was investigated. Environmental sampling was carried out within eight hospitals in England during t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…It is important to note, however, that emerging evidence suggests that fomite transmission may be a more significant route for SARS-CoV-2 than airborne transmission. 49,50 Another potential limitation of the present study is the setup of the 'salivary ducts' as these were positioned in a non-anatomical position. We chose this position (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that emerging evidence suggests that fomite transmission may be a more significant route for SARS-CoV-2 than airborne transmission. 49,50 Another potential limitation of the present study is the setup of the 'salivary ducts' as these were positioned in a non-anatomical position. We chose this position (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SARS-CoV-2 RNA was detected on 30 (8.9%) of 336 environmental surfaces. Moore et al (2020) found that toilet door handles, nurse call buttons, portable vital signs monitors, cell phones, bed rails, and bed controls were infected surfaces ( Moore et al, 2020 ). Other studies have approved that door handles, bathroom toilet seat cover, bathroom door handle were the most contaminated environment although the chi-square p-value is only 0.064 ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting feature in our study was the significant reduction of normal-flora in both SARS-CoV-2 patient groups such as Leptotrichia, Bacteroides, Fusobacterium, Chorynebacterium and Bernesiella spp., indicating the imbalance of microbiota (Figure 2D-2F). Moore et al 41 also found a significant reduction of Fusobacterium periodonticum in the nasopharynx during SARS-CoV-2 infections. Those bacterial flora found in the oral cavity may inhibit pathogenic bacteria by producing antimicrobial substances such as bacteriocins, lactic acid and hydrogen peroxide which might create a hostile condition for the pathogenic bacteria 30 .…”
Section: Discussionmentioning
confidence: 89%